Prototype Design of Palm Oil Fruit Collection Based on Automation Industrial Robotics using QFD Method - Zulfahmi Noor; Marvel Dwi Gulan Silindang; Dewi Risky Hariyono; Firta Handayani; Dino Moeslim Jujuryansyah; Anisa Suliyanti; Nurmasitya Kemalaintan; Muhammad Noor Arridho; Fauziah (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The manual collection of scattered palm oil fruits in plantation areas often causes worker fatigue and ergonomic risks. This study aims to analyze user requirements and design an automated robotic system for palm oil fruit collection using the Quality Function Deployment (QFD) approach. The proposed robot is designed to navigate autonomously between oil palm trees and detect fruit positions through sensors and intelligent camera integration. QFD is used to translate user needs into technical specifications for the robotic system. The analysis shows that several attributes are required, including high mobility on various terrains, a robotic arm for fruit collection and self-recovery when overturned, weather-resistant and easy-to-clean materials, an automated fruit collection mechanism, sufficient wireless power endurance, a solar-powered charging station, accurate fruit identification, a navigation system, and a fruit weight detection sensor. The highest improvement ratios are found in the navigation system, robotic arm, solar charging station, and weight detection sensor. These findings indicate that the proposed robotic system can meet user requirements and has the potential to improve collection efficiency, reduce worker workload, and support productivity in oil palm plantations.